The Role Of Religious Teaching In Building Student Morals - Nur Fadhilah; Cynthia Claudia (Proceeding International Seminar of Islamic Studies, 2019)
Education is the right of all children, including children with special needs in inclusive education programs, but in its application many problems are encountered. For this reason, this study aims to analyze the application of inclusive education programs in early childhood education institutions, precisely at Raudhatul Athfal An-Nahl Jakarta. This study uses a qualitative approach to the type of case study research. Data collection techniques used were observation, interviews, and documentation. Technical analysis of data using the Miles and Huberman interactive analysis model, as well as testing the validity of the data with the triangulation method. The results of this study found six steps in the application of inclusive education programs, the first, to understand the characteristics of students; second, set learning goals and targets; third, designing flexible learning materials; fourth, monitoring and evaluation; the fifth, divides the tasks and roles of the teacher, and the sixth, prepares resources. The conclusion of the research shows that the six steps in this practical application are able to overcome the problems of implementing inclusive education programs in early childhood education institutions.